Kielich YHWH jako metafora gniewu Bożego w księgach prorockich Starego Testamentu - Szmajdziński, Mariusz (Verbum Vitae, 2018)
One of the many metaphors used by the Prophets is that of the cup of YHWH (kôs YHWH). Thirteen prophetic oracles, either directly or indirectly, employ this metaphor. The result of drinking the cup of YHWH is drunkenness, staggering, reeling, dishonour and shame, the result of being made naked and being uncircumcised, vomiting, self-mutilation and desolation. The one who has to drink the cup is humiliated in front of his neighbours and enemies. Those entities condemned to drink God’s cup, as the metaphor is applied, include Jerusalem as well as foreign nations. This punishment is a final blow for them and so deals death to them, just as alcohol when it is drunk in excess. However, God, when He comes to show compassion, removes the cup and gives salvation, though this outcome pertains only to Jerusalem and not to foreign enemies.